THE EFFECT OF CAPITAL RATIOS, CREDIT RISK, AND INFLATION ON LIQUIDITY IN INDONESIAN ISLAMIC COMMERCIAL BANKS - Alda Fildza Amima; Rais Sani Muharrami (Journal of Applied Economics in Developing Countries, 2025)
This study explores the effect of Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), and inflation on liquidity of Islamic commercial banks in Indonesia. The results of the analysis show that NPF has a significant impact on liquidity, while CAR and inflation show no significant effect. This finding implies that effective credit risk management is essential for Islamic banks to maintain liquidity.  Therefore, Islamic banks should tighten the analysis of financing eligibility and conduct stricter monitoring of the financing portfolio to minimize NPF. Although CAR is important for assessing capital health, an increase in CAR does not directly improve liquidity, which suggests that Islamic banks should focus on cash flow management and asset quality. Since Islamic banks do not rely on interest rates, inflation does not have a direct impact on liquidity. In this context, recommended policies include improving staff training in risk analysis and developing strategies to diversify financing portfolios to reduce reliance on one market segment that may be more prone to risk. Thus, the main focus for Islamic banks is to strengthen credit risk management and improve risk analysis capabilities to ensure liquidity stability in the face of volatile economic challenges.